VALIDITAS MEDIA PEMBELAJARAN FLASHCARD BERBASIS AUGMENTED REALITY PADA MATERI SEL KELAS XI SMA - Mardin, Herinda; D. Mamu, Hartono; Husain, Ilyas; Yasser Arafat, Muhammad (Jurnal Biogenerasi, 2024)
Augmented Reality (AR)-based flashcard learning media is the latest innovation that presents attractive 3D visual animations. This technology can make complex and abstract concepts easier to understand, triggering students' creativity, interest and curiosity in learning. Thus, this media can be an alternative solution in overcoming various learning problems. The purpose of this study is to test the validity of Augmented Reality-based flashcard learning media on cell material in class XI SMA, to ensure its effectiveness in improving student understanding. This research method uses a research and development approach with the ADDIE development model. The results showed that the assessment of the validity of Augmented Reality-based flashcard learning media by material experts included, 93% feasibility aspects, 86% presentation components, 92% language, and 90% AR media, with an average of 90% which included the category "Very Valid." Media experts assessed aspects of display design 70%, text design 76%, and Augmented Reality images 73%, with an average obtained of 74% or "Valid". The validity results obtained from material experts and media experts show an average percentage of 83% on each aspect assessed, which is included in the "Very Valid" category. Based on the results of the study it can be concluded that Augmented Reality-based flashcard learning media is feasible to use to support the learning process.